Predictors of Mortality in Ventilated Neonates in Intensive Care Unit - Hossain, M Monir; Shirin, Mahfuza; Al Mamun, Mohammad Abdullah; Hasan, Md Nurul Akhtar; Sahidullah, Md (Bangladesh Journal of Child Health, 2010)
Background: A large number of neonates in intensive care unit require mechanical ventilation due to various conditions and have a high mortality. To reduce the high mortality in this group of neonates, identification of risk factors is important. Objective: This study was undertaken to find out the predictors of mortality in ventilated neonates in the Intensive Care Unit. Methods: This study was carried out in the Intensive Care Unit of Dhaka Shishu Hospital from March 2006 to November 2006. Neonates consecutively put on mechanical ventilation during the study period were enrolled. The enrolled neonates were divided into two groups; neonates who died after putting to the ventilator were in group-I and neonates who survived after receiving mechanical ventilation were in group-II. Clinical, biochemical and ventilator parameters were analyzed to find out the predictors of mortality of ventilated neonates. Results: During the study period total 51 out born very critically sick neonates were ventilated due to different causes. Out of these 51 neonates, 58.8% were male with a male to female ratio 1.42:1. Mean age, weight and gestational age were 5.3±6.5 days, 2171±796.2 gm and 34.8±4.1 weeks respectively. Out of 51 mechanically ventilated neonates enrolled for this study, 70.6% died. Factors significantly different in nonsurvivors were mean weight, mean gestational age, initial arterial pH and duration of hospital stay (p<0.05). Weight <2500gm, gestation <34weeks, initial pH <7.1, PaCO2 >60 mmHg, serum sodium <130 mmol/l, serum potassium <3.5 mmol/l and FiO2 >60% were significantly associated with mortality in neonates requiring mechanical ventilation (p <0.05). Significant relation with mortality was found in those neonates who developed complications during ventilation (p=0.01). Conclusion: Among the analyzed factors weight <2500gm, gestation <34weeks, initial arterial pH <7.1, O2 saturation<80%, PaCO2 >60mmHg, FiO2 >60%, hyponatremia, hypokalemia and complications during ventilation were the significant predictors of mortality in ventilated neonates in the intensive care unit. Key words: Neonates; mechanical ventilation; predictors of mortality. DOI: 10.3329/bjch.v33i3.5687 Bangladesh Journal of Child Health 2009; Vol.33(3): 77-82